UMP promotes environmental awareness through collaboration with KOA Chenan Cherah - Norhidayah, Mohamad (UMPSA, 2023)
CAMERON HIGHLANDS, June 24, 2023 - Recognizing the importance of environmental awareness, volunteers from KILAU Universiti Malaysia Pahang (UMP) and the indigenous community of Kampung Orang Asli (KOA), Chenan Cherah, Cameron Highlands, Pahang, successfully organized the Alam@UMP and 'Bersama Kasih' (together with love) Community Service programme by planting trees together with the local community.